2021
DOI: 10.1002/jmv.26948
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection or reactivation: Genome‐based two distinct SNP profile of SARS‐CoV2 repositivity in an Indian case

Abstract: To date, a large number of case reports have emerged claiming COVID-19 reinfection, some confirmed by the distinct viral genotypes in each episode. [1][2][3][4][5][6][7][8][9] This communication highlights a case report from Delhi, India, with two instances of SARS-CoV-2 where the second episode witness moderate illness after 73 days of the first SARS-CoV-2 positive episode (asymptomatic). A 52-year-old male individual was tested positive at a COVID health care unit [RT-PCR/ Ct-values (ORF1ab-36.04/E gene-36.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In total, 35 articles describing the clinical courses of 60 unique individuals were identified that met the criteria. 7 14 , 18 – 43 An additional 114 articles were identified following abstract screening, but were not included in the analysis because they did not have sufficient sequencing results to conclude that the cases were reinfections. In total, 60 cases of verified reinfection were identified in this search.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 35 articles describing the clinical courses of 60 unique individuals were identified that met the criteria. 7 14 , 18 – 43 An additional 114 articles were identified following abstract screening, but were not included in the analysis because they did not have sufficient sequencing results to conclude that the cases were reinfections. In total, 60 cases of verified reinfection were identified in this search.…”
Section: Resultsmentioning
confidence: 99%
“…In the 36 studies (n = 51) [8-10, 32-37, 39, 43-45, 47-54, 56, 57, 59-62, 64-69, 71-73], which reported details of patients' symptoms during the first infection, these commonly included cough (30, 62.3%), fever (31, 58.5%), headache (20, 37.7%), diarrhea (13, 24.5%), sore throat (12, 22.6%), myalgia (12,22.6%), dyspnea (11,20.8%), rhinitis (9, 17%), fatigue (7, 13.2%), chills (6, 11.3%), anosmia (5, 9.4%), ageusia (5, 9.4%), malaise (4, 7.5%), chest pain (4, 7.5%), nasal congestion (4, 7.5%), odynophagia (4, 7.5%), nausea (3 5.7%), vomiting (2, 3.8%), anxiety (2, 3.8%), lethargy (2, 3.8%), panic attacks (1, 1.9%), sneezing (1, 1.9%), confusion (1, 1.9%), body pain (1, 1.9%), arthralgia (1, 1.9%), exertional tachycardia (1, 1.9%), dizziness (1, 1.9%), and arthromyalgia (1, 1.9%), and 10 (18.9%) patients [31,33,36,41,46,48,55,70] were asymptomatic.…”
Section: Symptoms Of Reinfected Patientsmentioning
confidence: 99%
“…The NGS-enabled genome sequencing has been instrumental in identifying the viral clades, lineages, and the role of non-synonymous mutations in altering the protein structure [ 15 ]. SARS-CoV-2 genome analysis can help us identify novel variants, reinfection cases, and also track the source of infection [ 16 ].Genomic surveillance has been instrumental to conclusively prove the incidences of re-infection. The identified mutations have been studied in detail for their role in immune escape through functional studies to enhance and elucidate the mechanism [ 17 ].…”
Section: Introductionmentioning
confidence: 99%